People in the mountains : current approaches to the archaeology of mountainous landscapes - Pelisiak, Andrzej,; Nowak, Marek (Archaeologist),; Astaloș, Ciprian, (Archaeopress Publishing Ltd, 2018)
Mountain landscapes were first exploited by farming populations at the very beginning of the Neolithic. However, there are controversies regarding when and where these specific types of human behaviour developed as a result of adaptation processes to these special environments. The aim of this book is to present research results from different scientific contexts. To discuss these issues, and to study different aspects of human activity in the mountains and adjacent regions we incorporate archaeological, botanical, zooarchaeological and ethnological information.